Secondary attributes of psychological components to road traffic accident / Mohamad Ghazali Masuri, Khairil Anuar Md Isa and Nor Azmir Md Noor - Masuri, Mohamad Ghazali; Md Isa, Khairil Anuar; Md Noor, Nor Azmir (Shah Alam, 2015)
Driving play an important role in our life as people travel from one place to another place by using several mode transportation such as personal or public transportation. This makes traveling become a very important aspect in the quality of life (QOL). As an occupational therapist, we were involved in educating, promote, evaluate, modify and rehabilitate people to become an Independence individual since driving can be part of the important component in the occupational performance area. This topic is relevant to the occupational therapist with regards of the profession itself as a health prevention, health promotion, and health education. This study was conducted among UiTM Puncak Alam students population, and the results will be able to explain the perception of educated young adult drivers in Puncak Alam towards speeding and associated risk. The results could be used to provide information to the targeted population regarding the issues. Hence appropriate intervention and strategies can be planed to reduce the road crashes. Thus, from this study, the outcomes of this study will give benefits to the people and country so that the accidents rate can be decreased and save more life. Road traffic accident (RTA) will give a huge impact to the individual and communities that include socio life, economic and also may cause damage to the property. The impact of the road traffic accident to the person may be fatal or non-fatal injuries that may lead to disability. Road traffic accident will cause a lost to country due to the government need to spend the money for the cost of treatment and rehabilitation for the injured person. Therefore, a proactive measure needs to take account to reduce the rate of road traffic accident. This present study will identify the prevalence use of text messaging while driving among young adults and their risk perception towards that's behavior. Road traffic accident has become a great issue and health problem in worldwide. Currently ranked eight, it has been estimated that by 2030 road traffic accident will become the fifth leading cause of death in the world. According to World Health Organization, (2013), over 1.2 million people die annually on the world's road and between 20 and 50 million sustain non-fatal injuries due to road traffic crash. Based on research conducted by the University of Michigan, "Malaysia was ranked as the top of 25 most dangerous countries in the world road accident", with estimated that 30 fatalities per 100,000 individual (The Star, 2014). Besides, the number of the road accident and fatalities are an increase compared with last year in 2014 with 1557 people involve in the road accident, and 1696 were killed (Official Portal of Royal Malaysia Police, 2015). This high number of the road accident is quite worrying as this death and injury will give the negative impact on the family, community and also the country. These numbers of injuries keep arising every year and had become a frightening issue in health and may contribute to significant effect on people quality of life (Wan Ahmad Kamal, Masuri, Dahlan, & Md Isa, 2015). RTA frequently involves multi-level society, and this has become a demanding community issue where more serious participation is needed to improve driver's attitude in the future. RTA has a significant impact on quality of life and financial burden to the government and Malaysian society. The number of road traffic accidents among young adult is an alarming issue in Malaysia. Malaysian governments through relevant agencies have worked very hard to enforce all relevance acts related to it. One of the prime government objectives is to ensure safer Malaysian drivers in the future. To date, there were still a limited number of local research and evidence supporting the elements of driver's attitudes and behavior analysis had been conducted.